Transit-Oriented Development (TOD) planning analysis by integrating Geographic Information System (GIS) approach - Wan Mohd Najib, Wan Zafirah; Hj. Mohd. Noor, Norzailawati; Kadar Hamsa, Abdul Azeez (IIUM Press, International Islamic University Malaysia, 2020)
The development of TODs in Malaysia is still unclear because of no specific development and planning guidelines relating to TOD have been gazetted at the federal level. The objectives for this study are; (1) identifying land-use dimension to determine the potential of TOD development, (2) to analyse the potential of rail-based stations for TOD purposes based on five land-use dimension analysis, (3) to rank TOD typology of rail-based stations using GIS-MCDM technique and (4) to recommend the use of geospatial approach as a transportation planning solutions. The area of analysis will be within 400 meters radius from the rail-based stations in Shah Alam City Council. The analysis of research was evaluated on the land-use criteria comprising of coverage area, land availability, gentrification potential, density and diversity. The finding shows that the KTM Padang Jawa was identified as the most potential stations with scores of 80%. The least potential station is Skypark Link Subang Airport with scores of 40%. Result shows that the typology for two stations are determined as’ second-highest TOD intensity’ and ‘third-highest TOD intensity’. This study will provide a better understanding of how the land-use dimensions of TOD potential analysis are integrated into GIS application which is significant in many ways.